Thiol/Disulfide homeostasis in patients with rheumatoid arthritis - Tuzcu Ayca; Baykara Rabia Aydogan; Omma Ahmet; Acet Gunseli Karaca; Dogan Erdal; Cure Medine Cumhur; Sandikci Sevinc Can; Cure Erkan; Neşelioğlu Salim; Erel Ozcan (Sciendo, 2019)
Background. Oxidative stress may play an important role in rheumatoid arthritis (RA) etiopathogenesis. The thiol group is a very strong antioxidant. In this study, we aimed to investigate the presence of oxidative stress in patients with RA by evaluating thiol/disulfide homeostasis.